The Effect of Facilities on Motivation and Its Impact on Accounting Understanding - Ahmad Rivai; Sungguh Ponten Pranata; Zakia Fadila; Maya Syahlina; Berupilihen Br Ginting (Publisher Cv. Inara, 2021)
The purpose of this study is to determine the role of facilities on accounting understanding through motivation as an intervening variable. The research method is quantitative. The population and samples came from active students as many as 112 respondents. The sampling technique used was quota sampling. The results showed that the facilities indirectly affected students' accounting understanding through motivation at STIE Mahkota Tricom Unggul. This means that motivation has a role in mediating facilities on accounting understanding.